Forces Driving Inflation in the New EU10 Members - Stavrev, Emil. (Washington, D.C. : International Monetary Fund, 2009)
The paper analyzes the forces driving inflation in the new EU10 member countries. A significant part of headline inflation in these countries is due to common factors, such as price level convergence and EU integration. However, idiosyncratic factors have also played a role in the inflation process. These factors are related to the country-specific financial conditions, pass-through from foreign prices, and demand-supply situation in each country, although administered price adjustments and increases of indirect taxes associated with EU accession are also likely to have played a role.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet